Navigating through Complexity by Profiling the Main Threats to Sustainable Tropical Wetlands Management and Governance: A Case Study of Mityana District, Uganda - Matovu, Baker; Sarfo, Isaac; Bbira, Yasin; Yeboah, Emmanuel; Muhoozi, Yosia; Lukambagire, Isaac (Springer International Publishing, 2024)
Abstract Wetlands are crucial ecosystems that promote sustainable livelihood and biodiversity conservation, especially in tropical regions. However, recent studies have reported increasing threats to wetlands both environmental and human which threaten the provision and acquisition of several wetland benefts. Though there is recognition of the value of wetlands, in most local communities in Uganda; especially around the Lake Wamala region in Mityana district, there is still limited knowledge and research on the benefts of wetlands and the level of threat thus afecting wetland governance. This research addresses this gap by using participatory research to create a baseline inventory that could be used by wetland managers to identify the main wetlands threats to inform policy on how to develop participatory actions and local area-based management practices. The study was conducted in 14 sub-counties and a sample of 105 wetlands along the wetlands of Lake Wamala and River Mayanja wetlands system in Mityana District was captured. Study fndings revealed increased human threats to wetlands especially in the River Mayanja seasonal wetlands zone. The increased efects of environmental threats such as climate change are also altering permanent wetlands along Lake Wamala. Our developed inventory based on local participants’ perspectives revealed that since the level of damage to wetlands in Mityana especially the permanent wetlands is relatively low, a focus on developing new mapping, and a decentralized approach to wetland management that focuses on capacity building, development of wetlands action plans, increased support to local wetland authorities, and a system thinking approach in wetland threat identifcation and management could help in the regeneration of most wetlands zones.
Keywords: Wetland · Wetland resources and ecosystems · Wetland threats · Wetland action plans · Mityana district · Uganda